2019
DOI: 10.1007/s40279-019-01178-7
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Nordic Hamstring Exercise Intervention Volume on Eccentric Strength and Muscle Architecture Adaptations: A Systematic Review and Meta-analyses

Abstract: Background Although performance of the Nordic hamstring exercise (NHE) has been shown to elicit adaptations that may reduce hamstring strain injury (HSI) risk and occurrence, compliance in NHE interventions in professional soccer teams is low despite a high occurrence of HSI in soccer. A possible reason for low compliance is the high dosages prescribed within the recommended interventions. The aim of this review was to investigate the effect of NHE-training volume on eccentric hamstring strength and biceps fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 58 publications
(82 reference statements)
4
106
0
1
Order By: Relevance
“…Most interventions were conducted within applied settings; however, several studies failed to describe the additional training or provided limited information. It is important to include any concurrent training stimuli to fully assess if there were any outside interactions with any adaptations seen following a training intervention [197]. Most of the training interventions have reported positive effects on sprinting capabilities leading to the assumption that sprinting performance is easily improved with a variety of methods.…”
Section: Summary Of Interventions To Develop Short-sprint Performancementioning
confidence: 99%
“…Most interventions were conducted within applied settings; however, several studies failed to describe the additional training or provided limited information. It is important to include any concurrent training stimuli to fully assess if there were any outside interactions with any adaptations seen following a training intervention [197]. Most of the training interventions have reported positive effects on sprinting capabilities leading to the assumption that sprinting performance is easily improved with a variety of methods.…”
Section: Summary Of Interventions To Develop Short-sprint Performancementioning
confidence: 99%
“…This effect size was selected as recent meta-analytical review revealed that the eccentric hamstring strengthening results in large increases (effect sizes >1.0) in eccentric hamstring strength and BFlh fascicle length. 16 All participants self-reported as being recreationally active (>3 hours of physical activity per week). The inclusion criteria were the ability to descend actively to at least 50% of the full range of motion during the standard NHE.…”
Section: Participantsmentioning
confidence: 99%
“…When used longitudinally, eccentrically biased training can provide a range of benefits including enhanced concentric and eccentric strength, change of direction ability, sprint and jump performance, and decreased injury incidence . Moreover, a recent meta‐analysis concluded that the Nordic hamstring exercise (NHE) can induce positive changes in muscle architecture and strength . Notwithstanding the performance‐related benefits, the NHE has the ability to reduce hamstring injuries by up to 51% in a sample of 8459 athletes and is advocated within youth soccer injury prevention programs .…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, a recent meta-analysis concluded that the Nordic hamstring exercise (NHE) can induce positive changes in muscle architecture and strength. 25 Notwithstanding the performance-related benefits, the NHE has the ability to reduce hamstring injuries by up to 51% in a sample of 8459 athletes 26 and is advocated within youth soccer injury prevention programs. 27 This is particularly important when considering that hamstring strains account for 12% of injuries among 17 top fight European soccer teams 28 and is considered the most important injury risk factor.…”
Section: Introductionmentioning
confidence: 99%